The Facile Fabrication of Hollow Cu2O Nanoparticles Induced by the Kirkendall Effect on Cu@Ag Core‐Shell Nanoparticles. (27th July 2015) - Lu, Ying; Kang, Hyun Suk; Lim, Young S.; Lee, Byung Cheol; Kim, Sang‐Ho; Piao, Longhai
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10401-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>